Crystal structure and magnetic properties of the Gd8Ag19.5Al45.2 and Ho8Ag21.2Al43.3 compounds. (2nd December 2019) - Tyvanchuk, Yuriy; Stelmakhovych, Bohdan; Krachan, Tetyana; Baran, Stanisław; Szytuła, Andrzej
ABSTRACT: The crystal structures of the Gd8 Ag19.5(2) Al45.2(2) (Gd4 (Ag0.294 Al0.706 )32 Ag0.340 ) and Ho8 Ag21.2(2) Al43.3(2) (Ho4 (Ag0.323 Al0.677 )32 Ag0.252 ) compounds, which adopt the Yb8 Cu17 Al49 -type structure with the space group I 4/ mmm, have been investigated by means of the X-ray powder diffraction. The structures of the compounds are characterized by the silver/aluminum mixing on several atomic positions and the partial occupancy of silver atoms on one atomic position. dc and ac magnetic data indicate antiferromagnetic properties below 46.5 K for Gd8 Ag19.5 Al45.2 and 15 K for Ho8 Ag21.2 Al43.3 . In case of RE  = Gd an anomaly observed in its magnetic susceptibility at 3.5 K suggests a magnetic transition of the order-order type. A metamagnetic phase transition is detected for RE  = Ho.